2011
DOI: 10.2337/db11-0708
|View full text |Cite
|
Sign up to set email alerts
|

Greater Impact of Melanocortin-4 Receptor Deficiency on Rates of Growth and Risk of Type 2 Diabetes During Childhood Compared With Adulthood in Pima Indians

Abstract: Features of melanocortin-4 receptor (MC4R) deficiency have been observed to be more pronounced in childhood. Longitudinal data from a population-based study were used to separate the phenotypic effects of MC4R deficiency during childhood and adulthood. The MC4R exon was sequenced in 6,760 individuals of predominantly Pima Indian heritage, and discovered mutations were functionally assessed in vitro. Effects on BMI, height, and slope of BMI change were assessed during childhood (ages 5–20 years) and adulthood (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 34 publications
(67 reference statements)
2
53
1
1
Order By: Relevance
“…Heterozygous and homozygous mutations in MC4R are well documented in humans to lead to a syndrome of early-onset obesity, hyperinsulinemia, increased bone mineral density, and accelerated linear growth. (3, 4) Similarities between the obesity syndromes in mc4r and gnas exon 1 knockout mice, along with the coupling of the MC4R through G s α support the possibility of abnormal MC4R function in PHP-1a. Mice have paternal imprinting of gnas in the paraventricular nucleus of the hypothalamus, an important site of MC4R action.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Heterozygous and homozygous mutations in MC4R are well documented in humans to lead to a syndrome of early-onset obesity, hyperinsulinemia, increased bone mineral density, and accelerated linear growth. (3, 4) Similarities between the obesity syndromes in mc4r and gnas exon 1 knockout mice, along with the coupling of the MC4R through G s α support the possibility of abnormal MC4R function in PHP-1a. Mice have paternal imprinting of gnas in the paraventricular nucleus of the hypothalamus, an important site of MC4R action.…”
Section: Introductionmentioning
confidence: 84%
“…(3, 4) Both the MC4R and G s α murine models demonstrate insulin resistance and impaired glucose tolerance that may develop prior to the onset of obesity. (5-7) In our study, we found that 4 of 6 children with PHP-1a had already developed hyperinsulinemia and insulin resistance, however, we did not find evidence that that the insulin resistance in PHP-1a is more severe or earlier in onset than in obese controls.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate 1 h-PG and 2 h-PG as predictors of type 2 diabetes in Groups 1 and 2, proportional hazard analysis was used to calculate HRs for development of type 2 diabetes, adjusting for baseline age, sex, BMI and SWNA heritage status. The fraction of SWNA heritage (in eighths, ranging from 0/8 to 8/8) was determined from personal history and family data, as previously described [33]. For this study, SWNA heritage was considered a dichotomous variable (those with 8/8 SWNA heritage vs those less than 8/8 SWNA heritage).…”
Section: Methodsmentioning
confidence: 99%
“…16 Two variants were described as GOF in a prior study: V103I 17 and I251L. 17 One variant, F202L, 27, 28 was described as non-function-altering in prior studies.…”
Section: Methodsmentioning
confidence: 99%
“…Decreased stimulated cAMP generation previously reported. 16 Surface expression, ligand binding, and basal activity have not been reported.cCategorized as GOF because V103I previously reported to have decreased agouti-related peptide potency, while I251L has increased basal activity. 17 …”
Section: Figurementioning
confidence: 99%